2011
DOI: 10.1001/archsurg.2010.316
|View full text |Cite
|
Sign up to set email alerts
|

Better Weight Loss, Resolution of Diabetes, and Quality of Life for Laparoscopic Gastric Bypass vs Banding

Abstract: When performed in high-volume centers by expert surgeons, RYGB has a similar rate of overall complications and lower rate of reoperations than LB. With the benefit of greater weight loss, increased resolution of diabetes, and improved quality of life, RYGB, in these circumstances, has a better risk-benefit profile than LB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 51 publications
(74 reference statements)
2
38
0
5
Order By: Relevance
“…Resolution of diabetes was observed in 78% of the patients treated with Roux-en-Y gastric bypass who had diabetes before surgery, compared with 50% resolution in previously diabetic patients who received laparoscopic adjustable gastric banding. In a recent 2 cohort pair matched study of 200 obese patients, diabetes resolution occurred in 76% of patients who underwent RYGB compared with 50% of those who had LAGB [29]. Lee et al [30] have published the results of a RCT comparing gastric bypass versus sleeve gastrectomy in patients with BMI 25-35 kg/m 2 ; the remission rate for T2DM was 93% for patients who underwent RYGB compared with 47% for those who underwent sleeve gastrectomy.…”
Section: Comparative Efficacy Of Different Bariatric Proceduresmentioning
confidence: 99%
“…Resolution of diabetes was observed in 78% of the patients treated with Roux-en-Y gastric bypass who had diabetes before surgery, compared with 50% resolution in previously diabetic patients who received laparoscopic adjustable gastric banding. In a recent 2 cohort pair matched study of 200 obese patients, diabetes resolution occurred in 76% of patients who underwent RYGB compared with 50% of those who had LAGB [29]. Lee et al [30] have published the results of a RCT comparing gastric bypass versus sleeve gastrectomy in patients with BMI 25-35 kg/m 2 ; the remission rate for T2DM was 93% for patients who underwent RYGB compared with 47% for those who underwent sleeve gastrectomy.…”
Section: Comparative Efficacy Of Different Bariatric Proceduresmentioning
confidence: 99%
“…A study of adults by Campos et al 66 found that RYGB had a higher rate of early complications (11% vs 2%) but that LAGB had a significantly increased rate of late complications with reoperation occurring much more frequently (13% vs 2%). More concerning are 2 prospective studies 67,68 from Europe of long-term outcomes after placement of the LAGB.…”
Section: Laparoscopic Adjustable Gastric Bandingmentioning
confidence: 99%
“…A prospective two-cohort pair-matched study by Campos et al, compared 100 LAGB patients to 100 RYGB patients [18]. Preoperatively the mean BMI was 45.7 kg/m 2 in the LAGB group and 46.0 kg/m 2 in the RYGB.…”
Section: Malabsorptive Versus Restrictive Proceduresmentioning
confidence: 99%